Effects of gold catalysts and thermal evaporation method modifications on the growth process of Zn1-xMgxO nanowires - Yousefi, R.; Muhamad, M.R. (Academic Press Inc Elsevier Science, 2010)
In this paper, we investigate the roles of gold catalysts and thermal evaporation method modifications in the growth process of Zn1-xMgxO nanowires. Zn1-xMgxO nanowires are fabricated on silicon substrates with and without using a gold catalyst. Characterizations reveal that Mg acts in a self-catalyst role during the growth process of Zn1-xMgxO nanowires grown on catalyst-free substrate. The optical properties and crystalline quality of the Zn1-xMgxO nanowires are characterized by room temperature photoluminescence (PL) measurements and Raman spectroscopy, respectively. The Raman and PL studies demonstrate that the Zn1-xMgxO nanowires grown using the catalyst-free method have good crystallinity with excellent optical properties and have a larger band-gap in comparison to those grown with the assistance of gold. (C) 2010 Elsevier Inc. All rights reserved.